Mathematics for the imagination - Peter Higgins (OUP Oxford, 2002)
Mathematics for the Imagination provides an accessible and entertaining investigation into mathematical problems in the world around us. From world navigation, family trees, and calendars to patterns, tessellations, and number tricks, this informative and fun new book helps you to understand the maths behind real-life questions and rediscover your arithmetical mind.This is a follow-up to the popular Mathematics for the Curious, Peter Higgins\'s first investigation into real-life mathematical problems.This is a highly involving book which encourages the reader to enter into the spirit of mathematical exploration.